Rethinking the option of violence in politics and the fate of tiberius gracchus (2019)
The killing of Tiberius Gracchus along with hundreds of his supporters in factional violence has left an imprint of moral controversy. When perpetuated by the aggrieved or oppressed masses, violence is seen as an act of aggression or rebellion. However, it tends to be termed political expediency when initiated by the ruling power or its agency. Using interpretive approach, this paper sets aside justifying the murdering of Tiberius as removal of a potential tyrant who was causing public disturbance. The research, after highlighting how violence became imminent when other legitimate efforts at resolving political conflicts failed, shifts to the moral question arising from resorting to violence as the ultimate tool for achieving a political goal. Corrupt members of the Roman Senate and their supporters would share the view: ‘so perish also all others who do such things’. However, the paper notes the benefits of Tiberius’ agrarian reforms to the poor citizens and the potential benefits of the changes to the state. The conclusion is: the champion of the people had acted well enough but inconclusively to reach his goals. It remained for him and his supporters to stand against being outmaneuvered by the corrupt politicians. If violence had been used by Tiberius and his followers against the senate to succeed, the common people would have declared this as both morally justifiable and politically expedient. Hence, it is theorised that, when moral questions are unanswered in politics, violence looms and no one may have the monopoly of it